Industriearchäologie und Wirtschaftsgeographie - zur Erforschung der Industrielandschaft - Krings, Wilfried (ERDKUNDE, 1981)
In a first part the paper presents the new discipline of industrial archaeology (IA), its techniques of research and its aims, especially the efforts in preserving industrial monuments. The objects of investigation are shown in a synopsis based on a series of IA-publications from the United Kingdom and the Federal Republic of Germany. Apart from the mainly adopted systematic approach, IA is in part landscape study. Therefore, a relationship is established with the traditional landscape concept in economic geography. In a second part three main themes are suggested which could be studied by economic geographers wishing to co-operate with IA: - the selectivity of persistent industrial structures, - the qualitative variations of industrial landscape patterns, - the changing feature of regional economic activity during the Industrial Revolution. The last-mentioned topic should be adopted in order to verify, whether the intended systematic preservation plans are in conformity with the historical economic structures.